The Perception of Property Entrepreneurs in Surakarta City, Indonesia, on the Policy 2 Voluntary Disclosure Program - Wafi'ah Rizky Astarah; Asaprima Putra Karunia; Rihan Mustafa Zahri; Raymundo Patria Hayu Sasmita (AKUMULASI: Indonesian Journal of Applied Accounting and Finance, 2022)
This study aimed to determine the individual taxpayers’ perception of property entrepreneurs in Surakarta City regarding the Voluntary Disclosure Program (VDP) on interest in participating in the program. Data were collected by distributing online questionnaires through the WhatsApp application to 22 respondents for 17 days, resulting in 20 valid responses. Furthermore, the descriptive analysis method was used to process and elaborate the data. The results showed that the strongest component to increase the taxpayers’ interest in property entrepreneurs in Surakarta City is a sanction that ensnares tax evaders. Therefore, it is concluded that administrative and criminal tax sanctions are effective in making taxpayers comply with obligations and avoid tax evasion.